2021
DOI: 10.3389/fgene.2021.628890
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Prenatal Whole-Exome Sequencing to Identify a Novel Heterozygous Synonymous Variant in NIPBL in a Fetus With Cornelia de Lange Syndrome

Abstract: Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder characterized by a wide spectrum of abnormalities, including craniofacial dysmorphism, upper limb anomalies, pre- and post-natal growth restrictions, hirsutism and intellectual disability. Approximately 60% of cases are caused by NIPBL variants. Herein we report on a prenatal case presented with bilateral upper-extremity malformations and cardiac defects. Whole-exome sequencing (WES) was performed on the fetus–parental trio and a de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, accumulating evidence has shown that some specific synonymous variations can lead to diseases by influencing the mRNA stability and alternative splicing of exons ( Nackley et al, 2006 ; Sauna and Kimchi-Sarfaty, 2011 ), which should garner more interest. To date, only one fetal case with a NIPBL synonymous variant has been reported, providing limited phenotypic information related to a specific variant ( Qiao et al, 2021 ). This is presumably a result of the difficulty in recognizing fetal features in utero or the late onset of clinical manifestations, which do not appear during the early developmental stage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, accumulating evidence has shown that some specific synonymous variations can lead to diseases by influencing the mRNA stability and alternative splicing of exons ( Nackley et al, 2006 ; Sauna and Kimchi-Sarfaty, 2011 ), which should garner more interest. To date, only one fetal case with a NIPBL synonymous variant has been reported, providing limited phenotypic information related to a specific variant ( Qiao et al, 2021 ). This is presumably a result of the difficulty in recognizing fetal features in utero or the late onset of clinical manifestations, which do not appear during the early developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Most variants in these typical loci can change the splicing of exons and introns, resulting in specific diseases. Hence, to a large extent, they are unlikely to be ignored in routine analysis, as in the previously reported CdLS case with a synonymous variant at the last base of exon 27 in the NIPBL gene ( Qiao et al, 2021 ). Diseases caused by synonymous variations in deep exonic or introns are uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, a prospective study on use of WES for fetal structural anomalies demonstrated an additional diagnostic rate of 30% in fetuses with three (3) or more anomalies above routine chromosomal microarray. 9 The benefits of providing a definitive genetic diagnosis of ultrasound abnormalities are self-evident in terms of improved decision-making for pregnancy management, reproductive decision-making for current and future pregnancies, recurrence risk, and testing options.…”
mentioning
confidence: 99%